Cell detection at far ranges: supporting T(b) - Z relationships - Calheiros, R. V. [UNESP]; Machado, R. [UNESP]; Lima, M. A. [UNESP] (Wiley-Blackwell, 2005)
The Bauru radar detects inner cores of deep convective storm cells at long range, but relevant cell areas are left undetected. A procedure is in development to generate a more complete three-dimensional representation of the cell structure for cost-beneficial hydrological use at larger distances. A set of satellite microwave brightness temperature (T(b)) - radar reflectivity (Z) relationships, basic to the retrieval procedure, has been derived. Copyright (C) 2005 Royal Meteorological Society
Keywords: radar; satellite; reflectivity; brightness temperature